THE ENERGY FUNCTIONALS FOR ANISOTROPIC SCATTERING - DASSIOS, G.; KARADIMA, K. S. (Mathematical Methods In Scattering Theory And Biomedical Engineering, 2006)
Scattering theory for anisotropic media is a useful but mathematically very demanding subject. Previous work on scalar scattering in anisotropic media is presently extended to cover the effects of anisotropy on the energy functionals. So, using the fundamental solution, the integral representations, the modified radiation condition and the scattering amplitude, we generate the differential scattering cross-section, the absorption cross-section, the scattering cross-section and furthermore, is explored their interconnection. It is moreover interesting to see that all characteristics of the anisotropic medium are carried by a particular redirected gradient operator, which appears naturally whenever any kind of anisotropy is present.